Remediation quantum of organic amendments to immobilize potentially toxic heavy metals in wastewater-contaminated soils through maize cultivation - Zeeshan Manzoor, Muhammad; Sarwar, Ghulam; Ibrahim, Muhammad; Rehan, Saman Safdar; Hasnain, Zuhair; Rais, Afroz; Gul, Safia; Alfagham, Alanoud T.; Manono, Bonface O.; Mehmood, Kashf; Khan, Shahbaz (Frontiers in Environmental Science, 2024)
Wastewater is considered a good reservoir of mineral elements that can be used for agriculture, aquaculture, and some other activities after adopting suitable measures. The gap between supply and demand for water is increasing exponentially because of the abrupt boost to the world’s population. This poses a threat to human life as it has reached alarming levels in some parts of the globe. Normally, wastewater consists of liquid waste produced by commercial or industrial sources for daily use, consumption, and production. It is time to refocus our attention on a kind of circulating water system by reusing municipal wastewater for agricultural purposes, particularly irrigation. The recycled or treated water would be used as an alternative to fresh water. In the current study, the impact of various organic amendments was studied to mitigate the toxic effects of pollutants present in wastewater by cultivating maize as a test crop. The present study comprised five treatments replicated four times with a randomized complete block design under field conditions. In this experiment, the treatments included T1 (treatment 1) = control (wastewater-polluted soil without the application of any amendment), T2 = farmyard manure (FYM) at 2.5 tons ha-1 (hectare-1), T3 = FYM at 5.0 tons ha-1, T4 = compost at 2.5 tons ha-1, and T5 = compost at 5.0 tons ha-1. The application of FYM at 5.0 tons ha-1 (T3) was recorded as being the most effective as the maximum improvement was observed in soil characteristics such as pH, electrical conductivity (EC), sodium adsorption ratio (SAR), and organic matter, and for T3, these were 7.33, 2.22 dS m-1, 8.16, and 0.94%, respectively. T3 remained most superior in reducing the concentration of heavy metals in the soil; for example, lead, cadmium, nickel, and arsenic for T3 were 8.64, 1.34, 10.44, and 2.25 mg kg-1 (milligrams per kg), respectively. Maximum fresh biomass (fodder yield) of 9.98 tons ha-1 was harvested when FYM was applied at 5.0 tons ha-1 to the soil compared to 6.2 tons ha-1 in the control plot. The highest contents of nitrogen (1.20%), phosphorus (0.41%), and potassium (3.97%) were observed in maize plants for T3. In maize plants (T3), the concentration of lead, cadmium, nickel, and arsenic was reduced to levels of 1.92, 0.23, 2.28, and 1.25 mg kg-1, respectively. Therefore, it can be concluded from the findings of the experiment that the application of FYM significantly reduced heavy metal concentrations and improved soil health, along with maize crop growth and productivity.